Does board gender diversity affect firm performance? Empirical evidence from Standard & Poor's 500 Information Technology Sector - Liliana Nicoleta Simionescu; Ştefan Cristian Gherghina; Hiba Tawil; Ziad Sheikha (Financial Innovation, 2021)
The essence of this study is to investigate the influence of the board gender diversity on firms' accounting and market-based performance using a sample of Standard & Poor's 500 companies belonging to the information technology sector over 12~years. Using the pooled ordinary least squares (OLS) method, the outcomes provide evidence for a positive influence of women on corporate boards on both measures of company performance, except for the percentage of female executives in the case of return on assets (ROA). After estimating the fixed effects and random-effects through panel data, the econometric outcomes show no statistically significant association among board gender diversity and ROA but a positive influence of the number and percentage of women on board on price-to-earnings ratio.
Keywords: 650; Firm performance; Fixed-effects; Gender diversity; Pooled OLS; Random-effects